Persepsi pekerja terhadap pembangunan kerjaya di organisasi - Haslinda, Mustafa (University Malaysia Sarawak, UNIMAS., 2003)
The purpose ofthis study is to investigate the level ofperception and factors that affecting the employees' perception towards career development in Organization. This research has been conducted to three organizations in Terengganu they are Federal of Land Development Authority (Felda). Terengganu Authority Developing Center (KETENGAH). Jabatan Kerja Raya. This study is detennined ifthere are any di.fJerences between demographic characteristics and perception towards career development. The factors that being investigate here are training. job fit and recognition whereas the demographic factors is gender. age. educational level and length ofservice. AII the samples were from those organizations that are 20 from Felda. 20 from Ketengah and 19 from Jabatan Kerja Raya. The findings showed that the perceptions from all the respondents were positive. The findings also showed that there were no significant relationships exist between employees' perception towards career development and training. job fit and recognition. The studies also show that there are no significant differences between employees' perception towards career development based on their demographics characteristic such as gender. age. educational level and length of service except the age. Based on the research findings. researcher suggest that the management should place a great concern over factors has been increased the effectiveness of employee contribution and give higher perception to the employee towards career development. Besides that researcher also suggest that the future study should be more focus on other factors and should using other methods survey to defined how career development to be effecting at organization